Performance of a single-use gastroscope for esophagogastroduodenoscopy: Prospective evaluation - van der Ploeg, Koen; de Jonge, Pieter J.F.; Lammers, Wim J.; Koch, Arjun Dave; Vos, Margreet C.; Paulsen, Vemund; Aabakken, Lars; Bruno, Marco (Endoscopy International Open, 2024)
Background and study aims Reprocessing reusable endoscopes is challenging due to their non-sterilizable nature. Disinfection has been shown to have a significant risk of failure with serious consequences. Single-use endoscopes can eliminate contamination risk and reduce workflow delays caused by reprocessing. This study evaluated the clinical performance of single-use gastroscopes in patients undergoing esophagogastroduodenoscopy (EGD).Patients and methods In this case series, 60 patients underwent EGD using single-use gastroscopes, with 34 procedures in the endoscopy department and 26 in the intensive care unit. The primary outcome was successful completion of the intended EGD objective. Furthermore, certified endoscopists assessed device performance on a five-point Likert scale (ranging from 1-"much worse" to 5-"much better"), considering their experience with a reusable gastroscope.Results Successful completion of EGDs using only the single-use gastroscope was achieved in 58 of 60 cases (96.7%). In two cases, crossover to an ultra-slim endoscope was necessary to either reach the esophageal stenosis or to transverse the stenosis. Overall satisfaction was rated as comparable to reusable scopes in 51 of 56 cases (91.1%) and inferior in five cases (8.9%). The lower weight of the single-use gastroscope was rated as superior in 42 of 60 cases (70.0%). Drawbacks included reduced image quality (23 of 45 cases; 51.1%). Feedback included the absence of a freeze button, lens cleaning issues, and small image size.Conclusions Single-use gastroscopes exhibited a high EGD completion rate and effectiveness for various indications. Further research should focus on evaluating the implementation of single-use gastroscopes in a comprehensive context, considering clinical effectiveness, costs, and environmental impact.
Keywords: Endoscopy Upper GI Tract; Hygiene; Quality and logistical aspects; Performance and complications